Aktivitas Ekstrak Daun Kelor terhadap Respons Imun Humoral pada Mencit yang Diinfeksi Salmonella typhi (ACTIVITY OF KELOR LEAF EXTRACT ON HUMORAL IMMUNE RESPONSE IN MICE POST SALMONELLA TYPHI INFECTION) - Hefni, Mohammad; Rifa’i, Muhaimin; ., Widodo (Jurnal Veteriner, 2013)
The aim of this research was to analyze the activity of  kelor (Moringa oleifera Lam) leaf extract onhumoral immune response in mice infected with Salmonella typhi. Mice were divided into two groups : non-infected and infectedS. typhi groups. Each group was administered orally for 20 days with varied doses ofkelor leaf extract i.e. dose (0 mg/kg BW), dose 1 (14 mg/kg BW), dose 2 (42 mg /kg BW), and dose 3 (84 mg/kg BW).  Then all of the sample in infected groups were injected with 108 cells S. typhi. The humoralimmunity responses were determined by observing the number of lymphoid B cell (B220) and naive Thecell (CD4+CD62L+) by using software BD CellQuest Flowcytometry. The data were analysed using Two-Way ANOVA (P<0.05), with SPSS 16.0 for Windows.  The kelor leaf extract showed imunostimulatoryactivity by significantly improved the number of lymphocyte B cell (B220),  and naive Th Cell (CD4+CD62L+)in mice infected with S. typhi.  The lower doses (dose of 14 mg/kg BW, and 42 mg/kg BW) of kelor leafextracts was more effective than the highest dose (84 mg/kg BW). On the other  hand, the high dose showedimunosupresor activity on naive Teessor Th Cell.  However, immunosupressor activity on naïve Th cell wasobserved on the mice given the highest dose of extract.
Keywords: kelor (Moringa oleifera), Salmonella typhi, humoral immunity